Lessons learnt from pilot field test of a comprehensive advocacy program to support health promoting schools' project in Iran - Towhid Babazadeh; Behrouz Fathi; Abdolreza Shaghaghi; Hamid Allahverdipour (Tabriz University of Medical Sciences, 2017)
Background: Health promoting schools (HPS) project is currently being used in Iran but many challenges still lie ahead. The present study aimed, to test feasibility of implementing a comprehensive advocacy program (CAP) to overcome the obstacles and problems associated with the consummation of school health programs based on the HPS framework. Methods: This quasi-experimental study was performed through recruiting all schools that were enrolled in the national HPS program and located in Jolfa as the intervention group and all of the schools situated in the East Azerbaijan province as control. In order to collect data, Iranian Ministry of Health's checklists and external audit guidelines for HPS were utilized. In addition, to plan a CAP required data for coordinating fund raising activities including current rules and regulations regarding implementation of local health promotion interventions were collected. Results: Findings of the study revealed that the implemented CAP had improved all HPS dimensions' mean score in the intervention group. The observed change in the pre- and post-test score in the intervention group was significant (P < 0.05). The intervention was also successful in encouraging signing of an agreement among the participated organizations to be committed to pursue the adopted policies in facilitation of progress towards full implementation of the local HPS project. Conclusion: Commencing changes in the recruited schools' structure through coordinated multi-level activities is feasible and this must be considered as a priority where contextual determinants exist to motivate progress towards providing healthier educational settings for school aged children in Iran.